Praktični študij na Fakulteti za socialno delo - Mesec, Marko (Socialno delo, 2015)
Practicum is the most important part of training for social work students. Here users, students, mentors and teachers of social work meet. The key role in practicum is performed by students, whose motivation and self-initiative are the preconditions for their successful work. The Centre for Practical Studies has been operating at the Faculty of Social Work since 2007. Its task is to provide support to learning process, integration of teaching contents, support to mentors and students, and co-ordination of practical placement. Its aims are to form competent graduates of social work and to contribute to the development of the profession.
Keywords: social work; socialno delo; practicum; praksa; razvoj; development; co-operation; sodelovanje; methods; metode; competences; kompetence